Nonlinear elliptic equations by topological degree in Musielak-Orlicz-Sobolev spaces - AIT HAMMOU, Mustapha; LAHMI, Badr (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
We prove by using the topological degree theory the existence of at least one weak solution for the nonlinear elliptic equation Mathematics Subject Classification (2010): 35J60, 35D30, 47J05, 47H11. Received 26 December 2020; Accepted 03 June 2021. Published Online: 2023-12-11 Published Print: 2023-12-30